Acute and Subchronic Toxicity Profile of a Polyherbal Drug Used in Sri Lankan Traditional Medicine. (13th July 2020) - Liyanagamage, Donisha Shani Niharika Keembiya; Jayasinghe, Susanthi; Attanayake, Anoja Priyadarshani; Karunaratne, Veranja
Abstract : A polyherbal drug composed of leaves of Murraya koenigii L. Spreng, cloves of Allium sativum L., fruits of Garcinia quaesita Pierre, and seeds of Piper nigrum L. is a popular drug which has been used by indigenous practitioners in Sri Lanka for the treatment of diabetes mellitus and dyslipidemia. The acute toxicity assessment was conducted, following a single oral dose of 0.25–2.0 g/kg in healthy rats, and rats were observed up to 14 days. The hot water extract (1.0 g/kg) and the water : acetone extract (0.5, 1.0, and 1.5 g/kg) were administered to Wistar rats for 28 days in the subchronic study. Hypoglycemic and antihyperglycemic activities (dose response studies) of cold water, hot water, and water : acetone extracts of the polyherbal mixture were evaluated at the doses of 0.5, 1.0, and 1.5 g/kg in healthy and streptozotocin-induced diabetic rats (70 mg/kg, ip), respectively. Acute toxicity study showed that the polyherbal drug did not cause any change in animals throughout the experimental period of 14 days. The administration of the hot water extract and the water : acetone extract of the polyherbal drug for 28 days did not produce changes in the selected biochemical and hematological parameters in Wistar rats (p  > 0.05). The histological assessment corroborated the biochemical findings with no significant treatment-related changes in the kidney and liver. The treatment of polyherbal drug significantly lowered the serum glucose concentration compared to the diabetic control rats (p  < 0.05) while it did not lead to a severe reduction of glucose concentration in healthy rats. The hot water and water : acetone extracts of the polyherbal drug showed a statistically significant improvement on total area under the glucose tolerance curve in diabetic rats (p  < 0.05), reflecting dose-dependent antihyperglycemic effects of the drug. Based on the results, we conclude that the aforementioned antidiabetic polyherbal remedy is free of toxic/adverse effects at the equivalent human therapeutic dose in healthy Wistar rats and would be a safe therapeutic agent for long-term treatments.